2020
DOI: 10.3390/en13215711
|View full text |Cite
|
Sign up to set email alerts
|

Induction Heater Based Battery Thermal Management System for Electric Vehicles

Abstract: The life and efficiency of electric vehicle batteries are susceptible to temperature. The impact of cold climate dramatically decreases battery life, while at the same time increasing internal impedance. Thus, a battery thermal management system (BTMS) is vital to heat and maintain temperature range if the electric vehicle’s batteries are operating in a cold climate. This paper presents an induction heater-based battery thermal management system that aims to ensure thermal safety and prolong the life cycle of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…High thermal conductivity, mostly applied for high cooling demand [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. complexity, high cost, heavy, must store the fluid, viscosity, potential leaks, additives for anti-freeze & Boiling [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Liquidmentioning
confidence: 99%
See 3 more Smart Citations
“…High thermal conductivity, mostly applied for high cooling demand [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. complexity, high cost, heavy, must store the fluid, viscosity, potential leaks, additives for anti-freeze & Boiling [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Liquidmentioning
confidence: 99%
“…Many temperature ranges recommended for the use of lithium ion batteries are found in the literature, but, only a range between 15 °C and 35 °C is desired [5]. Some battery suppliers define four temperature ranges [1][2][3][4][5][6][7][8][9][10][11][12][13][14]: (1) (0-10 °C) decreased battery capacity and pulse performance, (2) (20-30 °C) optimal range, (3) (30-40 °C) faster self-discharge, and (4) (40-60 °C) irreversible reactions, with 60 °C being the upper safety limit under normal operating conditions. Another important point is the temperature uniformity between the battery cells in which the temperature difference must be less than 5 °C [4][5][6][7][8].Tete et al [4] revealed that at high temperatures, lithium-ion battery cells lost more than 60% of their initial energy after 800 cycles at 50 °C and lost 70% after 500 cycles at 55 °C.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Energy stored in lithium-ion batteries has many advantages [24]. However, significant limitations are the dependence of the distance range on charging infrastructures, battery capacity, and drive quality [25,26].…”
Section: Introductionmentioning
confidence: 99%